Improving the Students’ Mathematics Learning Outcomes of SMPN 23 Pekanbaru by Implementing a Problem-Based Learning Model - Husnul Khotimah; Yulvi; Yenni Elifa (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2022)
This study aims to determine the results of learning mathematics for class VIII students of SMP Negeri 23 Pekanbaru in the odd semester of 2022/2023 by applying a problem-based learning paradigm. This particular study is a classroom action study (CAR) focusing on Kemmis and McTaggart's design. The subject of this study was a group of 36 grade VIII students. This research was conducted in two cycles, and each was carried out in 4 meetings. The results of the study show that the development of a problem-based learning model can improve student learning outcomes by doing the following: 1) student organization on problems, namely the teacher will provide the necessary material; 2) guide students to learn, namely the teacher presents math problems; 3) investigate independent, or group investigations, namely students independently or in groups looking for solutions to the questions asked; 4) presentation or presentation of the results obtained; 5) Evaluation requires teachers and students to assess the results of group discussions.